Applications of Blockchain Technology in Securing Distributed Systems - Shedthi, Ashwini; Arunachalam, G.; Raj, M. Sundar; Tiwari, Mohit (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study examines the revolutionary potential of the blockchain within distributed network security, emphasizing decentralized control of identities, efficiency of transactions, and scale. The capacity analysis demonstrated the system's flexibility by sustaining a respectable transaction speed as the total number of nodes rose, using a thorough setup for experimentation. Confirmation times, a critical performance indicator for transaction efficiency, showed how responsive the system had been with average assurance times under different transaction loads fluctuating between 12 to 21 seconds. Strong security was demonstrated by the decentralized identification management algorithm, which successfully confirmed user identities and stopped unwanted access attempts. Inspired by related research, such as studies on Internet of Things (IoT) applications, electric power system cooperation, and drone electrical charging infrastructure, our work adds to the growing body of scholarship on applications for blockchain technology. Our approach stands out from the crowd thanks to comparison with previous research that emphasizes the importance of autonomous identity management in given system security. This research offers practical implications for healthcare, finance, along with energy sectors, as well as useful insights to feed industries that depend on autonomous systems. Our study adds significant information and insights that will help shape the bitcoin blockchain's role in improving safety and productivity in interrelated systems as it continues to influence the digital future.